COMPARISON ON ACCURACY OF LOGISTIC, GOMPERTZ AND VON BERTALANFFY MODELS IN PREDICTING GROWTH OF NEW BORN CALF UNTIL FIRST MATING OF HOLSTEIN FRIESIAN HEIFERS - Budimulyati S., L.; Noor, R.R.; Saefuddin, A.; Talib, C. (Diponegoro University, 2012)
The body weight records of 1221 heifers were used in this study collected from PT Taurus DairyFarm Sukabumi from year 2001 until 2011. The records that could be used for analysis were 373 out of1221 heifers, having completed data from birth to first mating period. Three different models i.e,Logistic, Gompertz, and von Bertalanffy were performed to analyze the growth rate of heifers. Theresults showed that the three models had different accuracy and heavily depend on age, environment andduration of recording. The body weights of sexual maturity and on certain ages were affected by theduration of recording. The Gompertz model was performed as the simpliest model in form ofcalculation. On the other hand, the Logistic was more difficult to calculate. All models indicated highaccuracy with the determination coefficient (R2) more than 90%. Based on the comparison, theGompertz and Logistic model are recommended for predicting the growth rate of heifers from birth tosexual maturity.